2009
DOI: 10.1016/j.adolescence.2009.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ explanations for romantic dissolutions: A developmental perspective

Abstract: Our objective was to examine the prevalence and developmental significance of romantic break‐ups in adolescence, a relatively unexplored area of study. We examined their occurrence in a sample of 910 adolescents, first noting the frequency of these events across age, gender, and romantic experience, and then analyzing the dissolution explanations provided by a subsample (N = 211) who experienced a break‐up within the past 6 months. Break‐ups were reported by 23% of youth, especially those with extensive romant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
130
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(140 citation statements)
references
References 32 publications
6
130
1
1
Order By: Relevance
“…We did not however investigate the motivation for the dissolution. Previous research indicates that those with high levels of Machiavellianism are more willing to engage in infidelity (Brewer & Abell, 2015) and avoid or reduce relationship commitment (Jonason & Buss, 2012); these are common causes of romantic relationship breakups (Betzig, 1989;Connolly & McIsaac, 2009). Hence future research should consider the relationship between Machiavellianism and this aspect of relationship dissolution.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not however investigate the motivation for the dissolution. Previous research indicates that those with high levels of Machiavellianism are more willing to engage in infidelity (Brewer & Abell, 2015) and avoid or reduce relationship commitment (Jonason & Buss, 2012); these are common causes of romantic relationship breakups (Betzig, 1989;Connolly & McIsaac, 2009). Hence future research should consider the relationship between Machiavellianism and this aspect of relationship dissolution.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…When relationships are terminated (i.e., a 'break up'), it is typically instigated by one member of the couple, with mutual agreement less prevalent (Hill, Rubin, & Peplau, 1976). Factors increasing the likelihood of relationship dissolution include a partner's failure to meet 2 expectations (e.g., sexual dissatisfaction), unequal commitment, a desire for freedom, and external factors (Connolly & McIsaac, 2009;Hill, Rubin, & Peplau, 1976;Sprecher, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively little research has also been conducted on romantic relationship dissolutions, a dating problem that was discussed by some study participants. The current study findings add to other efforts, for example, research on explanations of why adolescents dissolve romantic relationships, (i.e., Connolly and McIsaac 2009b) by shedding light on supports and barriers to dissolving a romantic relationship when this action is perceived as the best response to a dating problem.…”
Section: Practical Implications and Conclusionmentioning
confidence: 54%
“…When partners are unable to handle their disagreements, it is highly likely that their romantic needs are not met and they will move on to another relationship with the hope of fulfilling their needs with another partner. By interviewing adolescents who had recently experienced a romantic breakup, Connolly and McIsaac (2009b) showed that adolescents attributed their breakups to ''unfit'' relationships characterized by interaction difficulties such as poor communication and dishonesty, and not providing affiliation and intimacy. In contrast, a recent study by Ha, Overbeek, Lichtwarck-Aschoff, and Engels (2013) did not find conflict resolution to be associated with relationship longevity.…”
Section: Introductionmentioning
confidence: 99%